Place Attachment, Image, and Support for Marijuana Tourism in Colorado - Soo K. Kang (SAGE Open, 2019)
Colorado became the first state in the United States that passed the legalization of recreational (retail) marijuana with Amendment 64 in 2012. With this unprecedented tourism environment, it is imperative to understand different perspectives of stakeholders involved. In particular, residents’ view is important in that their attitude and behaviors plan and manage the design of marketing activities and sustainable development of the tourist place. Therefore, the purpose of the study is to examine the local residents’ image, attachment, and support of marijuana tourism as a result of the legalization of recreational marijuana in Colorado. Results of the study concluded that the highly attached residents held a positive image of their place, which in turn influence their support of marijuana tourism. Implications for industry professionals and state policy makers are presented.